Typification of Euphorbia candelabrum (Euphorbiaceae) and associated names - Figueiredo, Estrela; Smith, Gideon F. (Phytotaxa, 2020)
The valid publication of the name Euphorbia candelabrum Welwitsch (1855: 328) or E. candelabrum Welwitsch (1856: 251) (Euphorbiaceae) is subject to a request for a binding decision, which, following Art. 38.4 of the International Code of Nomenclature for algae, fungi, and plants (or Shenzhen Code, see Turland et al. 2018), provides the only means of permanently settling different views on the issue. As some typifications of associated names have not previously been effectively done, the following names are effectively typified here: E. candelabrum Trémaux ex Kotschy (1857: 169), E. venefica Trémaux ex Kotschy (1857: 173), and E. similis Berger (1907: 69). The type citation for E. conspicua Brown (1912: 600) is clarified. The nomenclatural status and type citations for E. confertiflora Volkens (1899: 266) and E. reinhardtii Volkens (1899: 263) are elucidated. These two names were not based on the same type and they are therefore not homotypic. Euphorbia confertiflora is a legitimate name.